Vinyl ester resin composition and resin molded article thereof
The vinyl ester resin composition, with ethyl methacrylate, styrene monomer, and carboxyl groups, addresses fluidity and contraction issues, resulting in improved mechanical properties and appearance of molded bodies.
Patent Information
- Application Number
- JP2021056699
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-30
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-03-30
AI Technical Summary
Conventional vinyl ester resin compositions face issues with fluidity, contraction, and mechanical characteristics during molding, leading to inadequate molded appearance and mechanical properties, especially when used as structural materials in automobiles.
A vinyl ester resin composition comprising vinyl ester resin, radical polymerization monomer, and low-shrinkage agents, specifically configured with ethyl methacrylate, styrene monomer, and carboxyl groups, which are copolymerized to enhance fluidity, reduce contraction, and improve mechanical characteristics.
The composition effectively suppresses contraction and enhances the mechanical properties and appearance of molded bodies, achieving excellent fluidity and mechanical characteristics.
Smart Images

Figure 0007622516000001 
Figure 0007622516000002 
Figure 0007622516000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a vinyl ester resin composition and a resin molded article thereof. [Background technology]
[0002] Vinyl ester resin compositions are widely used in applications such as paints, decorative panels, putties, resin concrete, construction materials, transport equipment, industrial equipment, etc. Vinyl ester resins are prepared, for example, by adding a curing agent (organic peroxide), a curing accelerator, etc. to a mixture of vinyl ester resin, which is a raw material, dissolved (diluted) in a radical polymerizable monomer such as styrene monomer. The resin composition is then cured and used as a cured product (molded body) in applications such as the decorative panels and construction materials.
[0003] Vinyl ester resin molded bodies are cured by sheet molding compound (SMC) molding. In SMC molding, glass fibers or carbon fibers with a length of about 10 to 50 mm are impregnated with a resin paste containing a mixture of resin, low-shrinkage agent, hardener, internal mold release agent, etc., and the sheet-like intermediate substrate is cut and weighed, charged into a mold, and further pressurized and heated to harden it to obtain a molded product. If the resin paste thickens when the resin and low-shrinkage agent are mixed, the impregnation property decreases, making it difficult to prepare the SMC substrate, so the resin paste must have fluidity.
[0004] The curing of vinyl ester resin compositions, like that of unsaturated polyester resin compositions, is basically a radical polymerization of the unsaturated double bonds of the resin and a radically polymerizable monomer, and therefore there is a problem that curing shrinkage of about 5 to 10 vol% occurs during curing, causing distortion and cracks in the molded product. In response to such a problem, Patent Document 1 discloses that a molded product with small molding shrinkage and excellent appearance can be obtained by using a specific AB type block copolymer as a low shrinkage agent in an unsaturated polyester resin. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-92646 Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, vinyl ester resin molded bodies have been used as structural materials for automobiles because they have chemical resistance, heat resistance, and impact resistance superior to unsaturated polyester resin molded bodies. Conventionally, when vinyl ester resin molded bodies are used as structural materials for automobiles, they are used as internal frameworks and the exterior is covered with steel plates, but due to the recent accelerated weight reduction of automobiles, the steel plates have been removed and vinyl ester resin molded bodies are exposed to the outside. Therefore, vinyl ester resin molded bodies are required to have excellent mechanical properties and molded appearance in addition to low shrinkage.
[0007] However, even when the conventionally disclosed low shrinkage agents are used in vinyl ester resin compositions, although the flowability is good, there are problems in that the molded appearance, mechanical properties and low shrinkage are insufficient.
[0008] An object of the present invention is to provide a vinyl ester resin composition which can suppress a decrease in the fluidity of a vinyl ester resin and shrinkage of a molded article during hot molding, and which can give a molded article having excellent appearance and mechanical properties. [Means for solving the problem]
[0009] The vinyl ester resin composition of the present invention comprises: A vinyl ester resin composition comprising (X) a vinyl ester resin, (Y) a radical polymerizable monomer, and (Z) a shrinkage reducing agent, The (Z) low shrinkage agent is a copolymer containing (z-1) a structural unit derived from an ethyl methacrylate monomer, (z-2) a structural unit derived from a styrene-based monomer, and (z-3) a structural unit derived from a carboxyl group-containing monomer, and when the total mass of the structural units derived from the (z-1) ethyl methacrylate monomer and the structural units derived from the (z-2) styrene-based monomer is taken as 100 parts by mass, the ratio of the structural units derived from the (z-1) ethyl methacrylate monomer is 30 to 70 parts by mass. department and the ratio of the structural unit derived from the styrene-based monomer (z-2) is 30 to 70 parts by mass.
[0010] The present invention also relates to a resin molded article obtained by curing the vinyl ester resin composition. Effect of the Invention
[0011] According to the present invention, it is possible to suppress the flowability of vinyl ester resin and the shrinkage of a molded article during heat molding, and to obtain a molded article having excellent appearance and mechanical properties.
[0012] Although the details of the mechanism of action of the vinyl ester resin composition according to the present invention are unclear, it is presumed as follows. However, the present invention does not need to be interpreted as being limited to this mechanism of action.
[0013] The vinyl ester resin composition of the present invention contains (X) a vinyl ester resin, (Y) a radical polymerizable monomer, and (Z) a shrinkage reducing agent. (Z) The shrinkage reducing agent is a copolymer containing (z-1) a structural unit derived from an ethyl methacrylate monomer, (z-2) a structural unit derived from a styrene-based monomer, and (z-3) a structural unit derived from a carboxyl group-containing monomer. The shrinkage reducing agent contains a structural unit derived from an ethyl methacrylate monomer (z-1) as described above, thereby obtaining a resin molded product having excellent mechanical properties. In addition, by using a structural unit derived from an ethyl methacrylate monomer (z-1) and a structural unit derived from a styrene-based monomer (z-2) in a specific ratio, a resin molded product having excellent molding shrinkage can be obtained. Furthermore, by containing a carboxyl group-containing monomer (z-3), the monomer is well compatible with the vinyl ester resin composition and can be well dispersed in the resin molded product, resulting in excellent flowability and molded appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] [(X) Vinyl ester resin] (X) The vinyl ester resin is usually obtained by converting an epoxy resin and an α,β-unsaturated monocarboxylic acid into a vinyl ester resin by a known method, and is also called an epoxy (meth)acrylate.
[0015] Examples of the epoxy resin include diglycidyl ethers of bisphenol A, bisphenol AD, bisphenol F, and bisphenol, as well as their high molecular weight homologues, phenol novolac polyglycidyl ethers, cresol novolac polyglycidyl ethers, etc. Furthermore, halogenated derivatives of these may also be used. The epoxy resins may be used alone or in combination of two or more.
[0016] Examples of the α,β-unsaturated monocarboxylic acid include acrylic acid, methacrylic acid, crotonic acid, tiglic acid, cinnamic acid, and unsaturated monocarboxylic acids derived from acrylic acid and / or methacrylic acid. The α,β-unsaturated monocarboxylic acids may be used alone or in combination of two or more kinds.
[0017] The reaction in the vinyl esterification is a reaction between the epoxy group of the epoxy resin and the carboxylic acid group of the α,β-unsaturated monocarboxylic acid. The reaction conditions are not limited in any way, but for example, the reaction is carried out at a reaction temperature of 80°C to 140°C, and if necessary, using a reaction catalyst. Examples of the catalyst include tertiary amines such as benzyldimethylamine, triethylamine, N,N-dimethylaniline, triethylenediamine, and 2,4,6-tris(dimethylaminomethyl)phenol, quaternary ammonium salts such as trimethylbenzylammonium chloride, and metal salts such as lithium chloride. The catalyst may be used alone or in combination of two or more.
[0018] The (X) vinyl ester resin can also be obtained by reacting a polyester having terminal carboxyl groups obtained from a saturated dicarboxylic acid and / or an unsaturated dicarboxylic acid and a polyhydric alcohol with an epoxy compound containing an α,β-unsaturated carboxylate group.
[0019] [(Y) Radical polymerizable monomer] Examples of the (Y) radical polymerizable monomer include vinyl monomers such as styrene, vinyl toluene, α-methylstyrene, vinyl acetate, methyl methacrylate, and ethyl methacrylate; allyl monomers such as diallyl phthalate, triallyl isocyanurate, and diallyl tetrabromophthalate; phenoxyethyl acrylate, 1,6-hexanediol acrylate, trimethylolpropane triacrylate, and 2-hydroxyethyl acrylate. The (Y) radical polymerizable monomer may be used alone or in combination of two or more. Among these, styrene, vinyl toluene, and the like are commonly used.
[0020] When the total mass of the vinyl ester resin (X) and the radical polymerizable monomer (Y) is taken as 100 wt %, the mass of the radical polymerizable monomer (Y) is preferably 10 to 60 wt %.
[0021] [(Z) Low shrinkage agent] (Z) The low shrinkage agent is a copolymer containing (z-1) a structural unit derived from an ethyl methacrylate monomer, (z-2) a structural unit derived from a styrene-based monomer, and (z-3) a structural unit derived from a carboxyl group-containing monomer.
[0022] (z-2) Styrene-based monomer is a monomer containing a styrene structure. Specific examples include styrene, vinyltoluene, α-methylstyrene, chlorostyrene, t-butylstyrene, divinylbenzene, vinylnaphthalene, etc., and styrene is particularly preferred.
[0023] As the carboxyl group-containing monomer (z-3), known monomers can be used. Examples include acrylic acid, methacrylic acid, crotonic acid, tiglic acid, and cinnamic acid. Of these, acrylic acid and methacrylic acid are preferred.
[0024] <(Z) Polymerization method of low shrinkage agent> (Z) The low shrinkage agent is a copolymer containing (z-1) a constituent unit derived from an ethyl methacrylate monomer, (z-2) a constituent unit derived from a styrene-based monomer, and (z-3) a constituent unit derived from a carboxyl group-containing monomer, and can be produced by a known method. It can also be produced by a method using a peroxide or a polymer peroxide as a polymerization initiator.
[0025] Peroxides and polymer peroxides are compounds having one or more peroxy bonds in one molecule. As peroxides and polymer peroxides, for example, those represented by the following formulas (1) and (2) can be used. Peroxides and polymer peroxides may be used alone or in combination of two or more.
[0026] [ka]
[0027] [ka]
[0028] The (Z) shrinkage reducing agent can be obtained by using the peroxide by a solution polymerization method, a bulk polymerization method, a suspension polymerization method, or an emulsion polymerization method. Examples of polymerization methods using the peroxide and polymer peroxide include the methods disclosed in JP-B-60-3327 and the like. For example, this polymerization method includes a first step of using a polymer peroxide as a polymerization initiator to polymerize the ethyl methacrylate monomer in a solution (polymerization solvent) to obtain a solution of a copolymer having a peroxy bond-containing A segment in which a peroxy bond has been introduced into the chain, and a second step of adding the styrene-based monomer and the carboxyl group-containing monomer to the obtained solution of the copolymer having the peroxy bond-containing A segment and polymerizing them to obtain a block copolymer having an A segment and a B segment.
[0029] In the polymerization method using the polymer peroxide, the styrene monomer and the carboxyl group-containing monomer may be added in the first step to obtain a solution of a copolymer having a peroxy bond-containing B segment, and then the ethyl methacrylate monomer may be added in the second step to polymerize. Between the first step and the second step, the copolymer having a peroxy bond-containing segment may be taken out of the reaction system as an intermediate, or may be subsequently block copolymerized without being taken out of the reaction system. Furthermore, the method of feeding the monomer mixture constituting the A segment or B segment is not particularly limited, and may be a lump-sum feed, a divided feed, or a continuous feed.
[0030] Examples of the solution (polymerization solvent) include water; alcohol-based solvents such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, s-butanol, t-butanol, and diacetone alcohol; alcohol ether-based solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, 3-methoxy-1-butanol, and 3-methoxy-3-methyl-1-butanol; ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ether-based solvents such as tetrahydrofuran and dioxane; ester-based solvents such as methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, t-butyl acetate, methyl lactate, and ethyl lactate; aromatic solvents such as benzene, toluene, and xylene; and amide-based solvents such as formamide and dimethylformamide. The polymerization solvents may be used alone or in combination of two or more.
[0031] The amount of the peroxide or polymer peroxide used is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the monomer component constituting the low shrinkage agent (Z). The temperature at which the polymerization reaction is carried out is appropriately changed depending on the type of the peroxide used, but in terms of industrial production, it is preferably 30 to 150°C, and more preferably 40 to 100°C. In particular, it is preferably 40 to 80°C for the polymerization reaction in the first step and 60 to 100°C for the polymerization reaction in the second step, and the polymerization temperature in the first step is preferably lower than the polymerization temperature in the second step. The polymerization time varies depending on the type and amount of the monomer used, but it is preferable that the polymerization reaction in the first step and the polymerization reaction in the second step are both in the range of 1 to 10 hours.
[0032] In the above polymerization, a suspending agent or the like may be used depending on the polymerization method. Examples of the suspending agent include hydrophilic organic polymers such as partially saponified polyvinyl alcohol, sodium polyacrylate, sodium polymethacrylate, and carboxymethyl cellulose; and poorly soluble inorganic salts such as calcium tertiary phosphate, barium sulfate, and calcium carbonate.
[0033] The weight average molecular weight (Mw) of the (Z) low shrinkage agent is preferably 50,000 or more, more preferably 100,000 or more, from the viewpoint of suppressing shrinkage of a molded article, and is preferably 1,000,000 or less, more preferably 500,000 or less, from the viewpoint of lowering the viscosity of the vinyl ester resin composition and improving the kneading workability.
[0034] <Composition ratio> In the vinyl ester resin composition of the present invention, when the total content of the vinyl ester resin (X) and the radical polymerizable monomer (Y) is taken as 100 parts by mass, the content of the low shrinkage agent (Z) is preferably 3 to 60 parts by mass, more preferably 5 parts by mass or more, from the viewpoint of molding shrinkage rate. Also, the content of the low shrinkage agent (Z) is preferably 50 parts by mass or less, particularly preferably 40 parts by mass or less, from the viewpoint of kneading workability of the vinyl ester resin.
[0035] The mass of the structural unit derived from the ethyl methacrylate monomer (z-1) and the structural unit derived from the styrene-based monomer (z-2) is 30 to 70 parts by mass (preferably 30 to 50 parts by mass) and the mass of the structural unit derived from the styrene-based monomer (z-2) is 30 to 70 parts by mass (preferably 50 to 70 parts by mass) per 100 parts by mass of the total of the structural units derived from the ethyl methacrylate monomer (z-1) and the styrene-based monomer (z-2).
[0036] In addition, the ratio of the structural unit derived from the carboxyl group-containing monomer (z-3) is 0.1 to 10 parts by mass relative to the total 100 parts by mass of the structural unit derived from the ethyl methacrylate monomer (z-1) and the structural unit derived from the styrene monomer (z-2). The ratio of the structural unit derived from the carboxyl group-containing monomer (z-3) is preferably 0.5 parts by mass or more, and 5 parts by mass or less.
[0037] Although the detailed factors are not clear, it is believed that by containing the (z-1), (z-2), and (z-3) components in the (Z) low shrinkage agent in the above-mentioned ranges, the (Z) low shrinkage agent takes on a special dispersion state in the (X) vinyl ester resin and radical polymerizable monomer, resulting in excellent low shrinkage. In addition, the (z-1) ethyl methacrylate monomer is believed to contribute to the formation of molded products with excellent mechanical properties. Furthermore, the (z-3) carboxyl group-containing monomer is believed to contribute to the fluidity of the resin and the appearance of the molded products.
[0038] The vinyl ester resin composition of the present invention may contain other additives generally used in vinyl ester resin compositions, such as fillers, curing agents, retarders, thickeners, antibacterial agents, internal release agents, reinforcing agents, dyes, pigments, UV absorbers, crosslinking agents, and antioxidants.
[0039] The filler may be any known inorganic or organic filler, and is not limited to a specific type. Examples of the inorganic filler include aluminum hydroxide, aluminum silicate, glass frit, silica, calcium hydroxide, calcium silicate, calcium carbonate, calcium sulfite, calcium sulfate, magnesium hydroxide, barium sulfate, titanium oxide, antimony trioxide, powdered talc, powdered quartz, calcite, diatomaceous earth, clay minerals, powdered chalk, marble, limestone, and borax. Examples of the organic filler include powdered cellulose and cotton powder. The filler may be composed of a single type or a combination of multiple types. The filler can usually be used in an amount of about 50 to 300 parts by mass per 100 parts by mass of the total of (X) vinyl ester resin, (Y) radical polymerizable monomer, and (Z) low shrinkage agent.
[0040] Examples of the curing agent include known organic peroxides such as ketone peroxides, peroxyketals, hydroperoxides, dialkyl peroxides, diacyl peroxides, peroxydicarbonates, peroxyesters, etc. The curing agent is usually used in an amount of about 0.1 to 5 parts by mass per 100 parts by mass of the total of (X) vinyl ester resin, (Y) radical polymerizable monomer, and (Z) low shrinkage agent.
[0041] When using the curing agent, it is possible to use a curing accelerator such as a tertiary amine such as N,N-dibutylaniline or tributylamine, an acetoacetate ester such as ethyl acetoacetate or propyl acetoacetate, or a cobalt salt such as cobalt naphthenate or cobalt octylate. The curing accelerator can usually be used in an amount of about 0.01 to 0.5 parts by mass relative to 100 parts by mass of the curing agent.
[0042] Examples of the retarder include known polymerization inhibitors such as hydroquinones such as hydroquinone, methylhydroquinone, 2-methylhydroquinone, and t-butylhydroquinone; benzoquinones such as p-benzoquinone and methyl-p-benzoquinone; catechols such as catechol and t-butylcatechol; phenols such as 2,6-di-t-butyl-4-methylphenol, 4-methoxyphenol, and cresol; and N-oxyls such as 1-oxyl-2,2,6,6-tetramethylpiperidin-4-ol. The retarder can usually be used in an amount of about 0.01 to 1 part by mass relative to 100 parts by mass of the total of (X) vinyl ester resin, (Y) radical polymerizable monomer, and (Z) low shrinkage agent.
[0043] Examples of the internal release agent include wax, polyvinyl alcohol solution, silicone-based release agent, zinc stearate, calcium stearate, etc. The internal release agent can usually be used in an amount of about 1 to 10 parts by mass per 100 parts by mass of the total of (X) vinyl ester resin, (Y) radical polymerizable monomer, and (Z) low shrinkage agent.
[0044] Examples of the thickening agent include isocyanate compounds. Examples of the isocyanate compounds include aromatic polyisocyanates, alicyclic polyisocyanates, araliphatic polyisocyanates, and aliphatic polyisocyanates. Examples of the aromatic polyisocyanates include tolylene diisocyanate (TDI) and 4,4'-diphenylmethane diisocyanate (MDI). Examples of the alicyclic polyisocyanates include hydrogenated xylylene diisocyanate (H6XDI), isophorone diisocyanate (IPDI), cyclohexane diisocyanate (CHDI), and hydrogenated 4,4'-diphenylmethane diisocyanate (H12MDI). Examples of the araliphatic polyisocyanates include xylylene diisocyanate (XDI), tetramethyl xylylene diisocyanate (TMXDI), and the like. Examples of the aliphatic polyisocyanate include 1,6-hexamethylene diisocyanate (HDI), etc. The thickener can usually be used in an amount of about 5 to 30 parts by mass per 100 parts by mass of the total of (X) vinyl ester resin, (Y) radical polymerizable monomer, and (Z) low shrinkage agent.
[0045] Examples of the reinforcing agent include glass fibers such as chopped strands, chopped strand mats, and roving cloth; carbon fibers, aramid fibers, etc. The reinforcing agent can usually be used in an amount of 10 to 50 parts by mass per 100 parts by mass of the total of (X) vinyl ester resin, (Y) radical polymerizable monomer, and (Z) low shrinkage agent.
[0046] The resin molded article of the present invention can be obtained by curing (molding) the vinyl ester resin composition. The curing (molding) can be performed using the vinyl ester resin composition alone, or can be performed using a composite material to cover the surface or the entirety of an article. The method for curing (molding) the vinyl ester resin composition is not limited in any way, and examples thereof include pultrusion molding, hand lay-up, filament winding, RTM, pin winding, infusion, hot (cold) press, spray-up, continuous press, and in the form of a prepreg, sheet winding, autoclave, etc. The curing (molding) temperature is about 45 to 170° C., and the curing time is several tens of seconds to several hours.
[0047] The molded article of the present invention can be used, for example, as automobile headlamp reflectors, fenders, roof panels, cylinder head covers, engine covers, motor sealants, motor coil sealants for HVs or EVs, gasoline tanks, laminates for electronic devices, breakers, and medical CT covers, and can be particularly suitably used as structural members for automobiles that are not covered with steel plates. EXAMPLES
[0048] The present invention will be described below with reference to examples, but the present invention is not limited to these examples in any way. <Production of low shrinkage agent> <Manufacturing example Z-1> A glass reactor equipped with a thermometer, a nitrogen inlet tube, a stirrer and a condenser was charged with 300 parts by mass of water, 15 parts by mass of a 1 wt% aqueous solution of partially saponified polyvinyl alcohol (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., "Gosenol KH-17") and 15 parts by mass of a 10 wt% aqueous dispersion of hydroxyapatite (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., "Supertite 10") . Next, 1 part of the peroxide of formula (1) was dispersed in the aqueous solution at room temperature for 1 hour, and then 30 parts by mass of ethyl methacrylate, 70 parts by mass of styrene and 0.5 parts by mass of methacrylic acid were charged. Then, polymerization was carried out for 3 hours at 55 ° C. under stirring while introducing nitrogen into the reactor. After that, it was cooled to room temperature, and the obtained polymer was washed with 130 parts by mass of 5 wt% hydrochloric acid and then with water, filtered, and then vacuum dried to obtain a white granular random copolymer.
[0049] <Manufacturing example Z-2> Production Example Z-2 was produced in the same manner as Production Example Z-1, except that the amounts of monomers were changed to those shown in Table 2.
[0050] <Manufacturing example Z-3> A glass reactor equipped with a thermometer, a nitrogen inlet tube, a stirrer and a condenser was charged with 300 parts by mass of water, 15 parts by mass of a 1 wt% aqueous solution of partially saponified polyvinyl alcohol (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., "Gosenol KH-17") and 15 parts by mass of a 10 wt% aqueous dispersion of hydroxyapatite (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., "Supertite 10") . Next, 1 part of the polymer peroxide of formula (2) was dispersed in the aqueous solution at room temperature for 1 hour, and then 30 parts by mass of ethyl methacrylate was charged. Then, while introducing nitrogen into the reactor, polymerization (first-stage polymerization reaction) was carried out at 65°C for 2 hours under stirring. After that, it was cooled to room temperature, and 70 parts by mass of styrene and 0.1 parts by mass of methacrylic acid were added to the reactor and dispersed at room temperature for 1 hour, and then polymerization (second-stage polymerization reaction) was carried out at 90°C for 1 hour under stirring while introducing nitrogen into the reactor. After cooling to room temperature, the resulting polymer was washed with 130 parts of 5 wt % hydrochloric acid, then with water, filtered, and then dried in vacuum to obtain a white granular block copolymer.
[0051] <Manufacturing examples Z-4~Z-8> Production Examples Z-4 to Z-8 were produced in the same manner as Production Example Z-3, except that the amounts of monomers were changed to those shown in Table 3.
[0052] <Comparative manufacturing examples Z'-1~Z'-2> Comparative Production Examples Z'-1 and Z'-2 were produced in the same manner as Production Example Z-1, except that the types or amounts of monomers were changed to those shown in Table 4. <Comparative manufacturing examples Z'-3~Z'-4> Comparative Production Examples Z'-3 to Z'-4 were produced in the same manner as Production Example Z-3, except that the types or amounts of monomers were changed to those shown in Table 5.
[0053] The weight average molecular weight of the low shrinkage additives obtained in Production Examples Z-1 to Z-8 and Comparative Production Examples Z'-1 to Z'-4 was measured. Specifically, a TOSOH HLC-8320GPC was used as the GPC system, and one TOSOH TSKgel Super Multipore H-RC was continuously installed as the column, the column temperature was set to 40°C, the standard substance was polystyrene, the developing solvent was tetrahydrofuran, the developing solvent was flowed at a flow rate of 1mL / min, 0.1mL of the sample solution with a sample concentration of 0.1wt% was injected, and the measurement was performed using the EcoSEC-WorkStation GPC calculation program.
[0054] In Tables 2 to 5, the parts by mass of each monomer are expressed as values calculated assuming that the total mass of (z-1) and (z-2) used in the above Production Examples and Comparative Production Examples is 100 parts by mass.
[0055] <Production of Vinyl Ester Resin Composition> 100g of a mixture containing vinyl ester resin and radical polymerizable monomer (manufactured by Nippon U-Pica, "Neopol 8051"), 5-50g of the low shrinkage agent obtained above, 15.5g of thickener (manufactured by Mitsui Chemicals, "Cosmonate LK"), 0.44g of retarder (5wt% solution of benzoquinone), 0.55g of hardener (1 / 1 mass ratio of NOF's "Perhexa C-75" and "Perbutyl I-75") were mixed and kneaded for 3 minutes at 300 rpm using a three-one motor (HEIDON600G). Then, 5.5g of carbon fiber (manufactured by Nippon Polymer Industries, "Milled Fiber CF-N 3mm") was added as a reinforcing agent and kneaded for 3 minutes at 300 rpm, and further, 11g of carbon fiber (manufactured by Nippon Polymer Industries, "Chopped Fiber CFMP-30RE") was added and kneaded for 5 minutes at 150 rpm to produce a vinyl ester resin composition.
[0056] <Preparation of vinyl ester resin molded body> The vinyl ester resin composition obtained above was wrapped in a PET film and allowed to stand for 24 hours at 40° C. Then, it was removed from the PET film and pressed at 140° C. / 10 MPa for 5 minutes to produce a disk-shaped vinyl ester resin molded product with a diameter of 90 mm and a thickness of 11 mm.
[0057] <Liquidity evaluation> Using a TVB-15 viscometer (manufactured by Toki Sangyo Co., Ltd.), the flowability of a mixture of 100 parts by mass of a mixture containing vinyl ester resin and radical polymerizable monomer and 5 to 50 parts by mass of a low shrinkage agent was measured at a rotation speed of 1.5 rpm for a measurement time of 5 minutes using a TM rotor (M4). The pass standard was 800P or less.
[0058] <Evaluation of the appearance of molded products> Evaluation was carried out according to the three-level criteria shown in Table 1. ◎ or ◯ was the pass criterion.
[0059] <Evaluation of molding shrinkage rate> The mold shrinkage was measured according to JIS K 6911. A mold shrinkage of 0.20 vol% or less was set as the pass criterion.
[0060] <Evaluation of tensile strength> The tensile strength was evaluated based on JIS K 7054. A tensile strength of 200 MPa or more was set as the pass standard.
[0061] [Evaluation Results] Tables 6 and 7 show the evaluation results of Examples 1 to 11 and Comparative Examples 1 to 4.
[0062] [Table 1]
[0063] [Table 2]
[0064] [Table 3]
[0065] [Table 4]
[0066] [Table 5]
[0067] [Table 6]
[0068] [Table 7]
[0069] As is clear from the results in Tables 2, 3 and 6, all of Examples 1 to 11 were excellent in flowability, molding shrinkage rate, molded article appearance and tensile strength.
[0070] On the other hand, as is clear from the results in Tables 4, 5 and 7, in Comparative Examples 1 to 4, the balance of these performances was insufficient. Specifically, in Comparative Example 1, the low shrinkage agent did not contain the component (z-2), and therefore low shrinkage properties were not exhibited. In Comparative Example 2, since the amount of the (z-1) component in the low shrinkage additive was small, a decrease in tensile strength was observed. In Comparative Example 3, since the low shrinkage agent did not contain the component (z-3), a deterioration in the appearance of the test piece was observed. In Comparative Example 4, since the low shrinkage agent did not contain the component (z-1), low shrinkage was not exhibited. Also, a decrease in tensile strength was observed.
Claims
1. A vinyl ester resin composition comprising (X) a vinyl ester resin, (Y) a radical polymerizable monomer, and (Z) a shrinkage reducing agent, The (Z) low shrinkage agent is a copolymer containing (z-1) a structural unit derived from an ethyl methacrylate monomer, (z-2) a structural unit derived from a styrene-based monomer, and (z-3) a structural unit derived from a carboxyl group-containing monomer, and is characterized in that, when the total mass of the structural units derived from the (z-1) ethyl methacrylate monomer and the structural units derived from the (z-2) styrene-based monomer is taken as 100 parts by mass, the ratio of the structural units derived from the (z-1) ethyl methacrylate monomer is 30 to 70 parts by mass, and the ratio of the structural units derived from the (z-2) styrene-based monomer is 30 to 70 parts by mass.
2. The vinyl ester resin composition according to claim 1, characterized in that when the total mass of the structural unit derived from (z-1) an ethyl methacrylate monomer and the structural unit derived from (z-2) a styrene-based monomer is 100 parts by mass, the mass of the structural unit derived from (z-3) a carboxyl group-containing monomer is 0.1 parts by mass or more and 10 parts by mass or less.
3. 3. The vinyl ester resin composition according to claim 1 or 2, wherein the low shrinkage agent (Z) is a block copolymer comprising (z-1) a segment A containing a structural unit derived from an ethyl methacrylate monomer, (z-2) a segment B containing a structural unit derived from a styrene-based monomer and (z-3) a structural unit derived from a carboxyl group-containing monomer.
4. The vinyl ester resin composition according to any one of claims 1 to 3, characterized in that a mass of the low shrinkage agent (Z) is 3 parts by mass or more and 60 parts by mass or less, when a total mass of the vinyl ester resin (X) and the radical polymerizable monomer (Y) is 100 parts by mass.
5. A resin molded article obtained by curing the vinyl ester resin composition according to any one of claims 1 to 4.
Citation Information
Patent Citations
Low-shrinkage unsaturated polyester resin composition
JP1982164114A
Unsaturated polyester resin composition and its production
JP1999092646A
Vinyl ester resin composition having low shrink properties
JP2000154295A
Block copolymer latex and method for producing the same
JP2001240635A